Boško Buha i Pavlik Morozov: novi (jugoslavenski / sovjetski) čovjek u tijelu malenoga dječaka - Lugarić Vukas, Danijela (Array, 2014)
Pavlik Morozov and Boško Buha are the first young heroes-victims in Soviet and Yugoslav cultures respectively who can be observed as models in the process of construing the New Man. These two New Men in a little boy’s body surprisingly resemble each other on several levels, ranging from visual representation to the articulation of their life paths in cultural texts. Both of them were brave under age fighters originating from the province who perished due to their loyalty to ideological regimes, thus becoming victim-idols used by political elites for the purposes of political manipulation. However, whereas Morozov served as an ideal model for the articulation of different Soviet ideas of the New Man, the image of Buha was a consequence of an entirely different political project and embodied one of the key ideas of the Yugoslav socialism: the one of fraternity and equality. This research paper covers several relevant questions by analyzing different cultural texts whose protagonists are Pavlik Morozov and Boško Buha. Firstly, to which extent was Morozov known in the cultures of the former Yugoslavia and did he serve the political elites as a model for the production of a Yugoslavian prototype of a young sacrifice for the greater good, i.e. for the creation of a (Soviet and/or Yugoslav) New Man in a little boy’s body even in spite of Tito’s “No” to Stalin? Secondly, to which “invented traditions” (Hobsbawm) do these two models refer and why was the Yugoslav government unable to “transfer” the model of Morozov in an unaltered form into the Yugoslav cultural discourse?